A STUDY OF INVESTOR’S BEHAVIORS TOWARDS SELECTED GOVERNMENT SCHEMES - Mrs. Priyamwada Saxena Dr.Madhuri Puranik (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
India is incrustation of inflation as unremitting delinquent and the government is unambiguous to mark conjecturing strategy to diminution or to sustain upsurge in accumulative proposal. Investments are both imperative and convenient in the milieu of the present-day conditions. Some dynamics that have made investment verdicts progressively imperative are elongated life prospect or scheduling for sequestration, accumulative tariffs of assessment, high interest rate of inflation, grander revenues and readiness of an intricate number of speculation channels. Investment verdicts are momentous to the emeritus folks between ages of 60-65 as for stretched life probability. Investment is a strategic system of security tapping one’s reserves into diverse vents to acquire a worthy reoccurrence. The pecuniary diligence has two notions on transactional deeds. One is hoard and the other is monies. There is a massive commonality between the two perceptions though it terms of accomplishment. Investment means any coinage that is expended today in the anticipation of pecuniary doles that may be procured in a forthcoming time edging. People should cultivate the convention of crafting speculation at any juncture of life. Redeemable coinage is a hoary manner so the people should endow their coinage to get maximum yields. The financiers should have chockfull acquaintance of the savings preferences to elude any forfeiture in future. The depositor should be vigilant what, where, why, when and how to make outlay apathetic speculation opportunities.